MIMO H-infinity control of three-axis ship-mounted mobile antenna systems - KUSEYRİ, İBRAHİM SİNA (TAYLOR & FRANCIS LTD, 2018)
The need for on-line information in any environment has led to the development of mobile satellite communication terminals. These high data-rate terminals require inertial antenna pointing error tolerance within fractions of a degree. However, the base motion of the antenna platform in mobile applications complicates this pointing problem and must be accounted for. Gimbaled motorised pedestals are used to eliminate the effect of disturbance and maintain uninterrupted communication. In this paper, a three-axis ship-mounted antenna on a pedestal gimbal system is studied. Based on the derived dynamic model of the antenna pedestal multi input-multi output PID and H-infinity linear controllers are designed to stabilise the antenna to keep its orientation unaltered towards the satellite while the sea waves disturb the antenna. Simulation results are presented to show the stabilisation performance of the system with the synthesised controllers. It is shown through performance comparison and analysis that the proposed H-infinity control structure is preferable over PID controlled system in terms of system stability and the disturbance rejection.
Keywords: Modelling; mobile antenna; simulation; MIMO control; H-infinity control; SATELLITE TRACKING ANTENNA; ROBUST ADAPTIVE-CONTROL; MOTION SIMULATOR